Genome-wide analysis in the search for candidate genes associated with meat productivity traits in meat-and-dairy goats - M. I. Selionova; A.-M. M. Aibazov; A. A. Sermyagin; A. A. Belous; N. A. Zinovieva (Теория и практика переработки мяса)
The development of the tourism cluster in the North Caucasus causes the expansion of product range with high consumer characteristics, in particular, a sustainable offer of dairy and meat products labeled as environmentally friendly. In the range of such products with high dietary properties, a special role may be played by goat meat obtained from Karachay goats, which are the most common meat-and-dairy goats in the region. The aim of the work was to search for candidate genes associated with live weight and meat productivity of Karachay goats. GWAS analysis using Goat 50K BeadChip high-density DNA microarray determined a genome-wide level of significance for six SNPs located on chromosomes 5, 6, 10 and 16 associated with the live weight of young animals (4 and 8 months old). Three of the six SNPs within the ± 200 kb region were localized to HMGA2, CRADD, and MAX genes. These genes were selected to study the meat productivity traits of young goats with different genotypes. It was found that in the locus linked with HMGA2 gene, young goats with GG genotype were characterized by the best indicators of meat productivity. Compared to AA genotype animals, they had superiority in pre-slaughter weight, slaughter carcass weight, slaughter yield, boneless meat weight and loin eye area by 8.9%, 13.6%, 4.3% (P<0.05), 10.5% (P<0.05) respectively. Young goat meat of this genotype was characterized by the high protein content of 22.56% and low fat content of 9.12%. For the CRADD gene, animals with GG genotype had a higher pre-slaughter weight, slaughter weight, slaughter carcass yield, boneless meat weight and loin eye area. Animals with AG genotype were characterized by the lowest indicators. According to the above characteristics, the difference between the compared genotypes was 15.8%, 25.7% (P<0.01), 8.4% (P <0.05), 18.3%, and 15.7% (P 0.01) respectively. There were no significant differences in the chemical composition of muscle tissue between animals of different genotypes. HMGA2 and CRADD genes are promising for further research of Karachay goats breeding to increase meat productivity and meat quality.